Malondialdehyde as a Prognosticating Marker for Staging of HIE - A Prospective Cohort Study (International Journal of Child Health and Nutrition, 2024)
Introduction: Prediction of outcomes of asphyxiated neonates is imperative. Timely intervention and effective resuscitation are beneficial for intact neurodevelopmental outcomes. In this study, we assessed the level of oxidative stress at birth in cord blood and correlated it with the Hypoxic Ischemic Encephalopathy (HIE) staging and outcomes.Methodology: This Prospective Cohort Study was conducted between January 2020 and June 2022. All neonates requiring resuscitation at birth were enrolled in a study group. The control group included neonates who did not require resuscitation. Cord blood was collected at birth, centrifuged, serum separated, and stored at -200C. Malondialdehyde (MDA) was read at 535nm on spectrometry.Results: 102 neonates were enrolled, among which 29 neonates were asphyxiated and 73 non-asphyxiated. The cord blood mean MDA level was significantly high in Severe HIE, with a p-value of